Non-paretic lower limb constraint with a step decreases the asymmetry of vertical forces during sit-to-stand at two seat heights in subjects with hemiparesis - Rocha A.D.S.* (2010)
This study investigated the effects of non-paretic leg constraint by a step, combined with two different seat heights, on weight-bearing on the paretic leg and reduction of asymmetry during STS. Thirteen adult subjects (60.4±5.7 years) were selected, with chronic hemiparesis (43.7±50 months) due to stroke. Two force plates were used to analyze the vertical force (Fz) in the standing position and during STS. Individuals were instructed to rise from an instrumented bench at two seat heights, 100% (normal) and 130% (elevated) of knee height with four foot positions: (1) spontaneous (SPO); (2) symmetrical (SYM); (3) asymmetrical (ASY; non-paretic limb in front of paretic); and (4) step (STP; non-paretic limb supported on a step and paretic at ground level). A reduction of asymmetry occurred during STS movement when the non-paretic leg was constrained by a step compared with positions SPO (p<0.001), SYM (p<0.001) and ASY (p= 0.02) at the normal seat level. Raising seat height to 130% increased asymmetry in the SPO condition (p= 0.01); however, this effect was reversed in the ASY and STP conditions. Constraint of the non-paretic leg by a step is presented as a potential therapeutic route to a less asymmetrical STS. Together with a higher seat level this can benefit the training of individuals with hemiparesis unable to keep the paretic foot backward during STS from a standard seat height. © 2010 Elsevier B.V.